Peranan Promosi dalam Meningkatkan Keikutsertaan Masyarakat dalam Program Penyelenggaraan Jaminan Sosial Ketenagakerjaan Studi Kasus di BPJAMSOSTEK Kantor Cabang Palembang - Triana Agustini; Raisa Putra (UNIVED Press, 2022)
The purpose of this study was to determine how the effect of promotion in order to increase community participation in the program of administering employment social security. The BPJS Employment Program is a social security program provided to workers. Based on Article 4 of Law no. 24 of 2011 concerning Social Security Administering Bodies, BPJS Organizes a national social security system based on the principles: mutual cooperation, non-profit, openness, prudence, accountability, portability, mandatory membership, mandated funds, and the results of the management of the Social Security Fund are used entirely for program development and to the greatest extent possible. The Central Statistics Agency of South Sumatra Province noted that for the population of South Sumatra there were more than 8.5 million, as of February 2020 consisting of a workforce of 4.33 million, who worked as many as 4.16 million in the formal sector, while in the informal sector in the micro-enterprise sector. small and medium enterprises (MSMEs) as many as 163,291. Looking at data from BP Jamsostek Palembang Branch, currently participants who follow the BPJamsostek program have only reached 2.3 million workers (27%) of the total number of potential workers reaching 8.5 million workers (in Sumbagsel), both Wage Recipients (PU), Non-Wage Recipients (BPU) and Construction Services (Jakon). Specifically for the coverage share participation for the province of South Sumatra with details of 2,916,275 participants, and the total participation in South Sumatra 7,952,597 (this figure includes the provinces of South Sumatra, Lampung, Bengkulu, Jambi, and Bangka Belitung).